FTD-associated mutations in Tau result in a combination of dominant and recessive phenotypes. - Law, A.D.; Cassar, M.; Long, D.M.; Chow, E.S.; Giebultowicz, J.M.; Venkataramanan, A.; Strauss, R.; Kretzschmar, D. (Neurobiology of Disease, 2022)
Although mutations in the microtubules-associated protein Tau have long been connected with several neurodegenerative diseases, the underlying molecular mechanisms causing these tauopathies are still not fully understood. Studies in various models suggested that dominant gain-of-function effects underlie the pathogenicity of these mutants; however, there is also evidence that the loss of normal physiological functions of Tau plays a role in tauopathies. Previous studies on Tau in Drosophila involved expressing the human Tau protein in the background of the endogenous Tau gene in addition to inducing high expression levels. To study Tau pathology in more physiological conditions, we recently created Drosophila knock-in models that express either wildtype human Tau (hTauWT) or disease-associated mutant hTau (hTauV337M and hTauK369I) in place of the endogenous Drosophila Tau (dTau). Analyzing these flies as homozygotes, we could therefore detect recessive effects of the mutations while identifying dominant effects in heterozygotes. Using memory, locomotion and sleep assays, we found that homozygous mutant hTau flies showed deficits already when quite young whereas in heterozygous flies, disease phenotypes developed with aging. Homozygotes also revealed an increase in microtubule diameter, suggesting that changes in the cytoskeleton underlie the axonal degeneration we observed in these flies. In contrast, heterozygous mutant hTau flies showed abnormal axonal targeting and no detectable changes in microtubules. However, we previously showed that heterozygosity for hTauV337M interfered with synaptic homeostasis in central pacemaker neurons and we now show that heterozygous hTauK369I flies have decreased levels of proteins involved in the release of synaptic vesicles. Taken together, our results demonstrate that both mutations induce a combination of dominant and recessive disease-related phenotypes that provide behavioral and molecular insights into the etiology of Tauopathies.